HUBUNGAN ANTARA KETERLIBATAN ORANG TUA DAN LINGKUNGAN BELAJAR DENGAN PRESTASI BELAJAR FISIKA SISWA KELAS X MIPA SMA NEGERI DI KOTA AMLAPURA - Muhamad Ramadhan; Ni Ketut Rapi; Dewi Oktofa Rachmawati (Universitas Pendidikan Ganesha, 2022)
This study aims to describe the relationship between: 1) parental involvement with learning achievement, 2) learning environment with learning achievement, 3) parental involvement and learning environment simultaneously with physics learning achievement. This research is a correlational study with an ex post facto design. The population of this study were 314 students of class X MIPA SMA Negeri in Amlapura City. Determination of the sample using proportional random sampling technique and obtained a total sample of 176 students. The instruments used in collecting data are questionnaires and multiple choice tests. Statistical methods used for data analysis are product moment correlation analysis, simple linear regression, and multiple linear regression. The results of this study indicate that there is a positive and significant relationship between parental involvement and learning achievement (r=0.426). There is also a positive and significant relationship between the learning environment and learning achievement (r=0.444). The two predictors simultaneously also showed a positive and significant relationship with learning achievement (r=0.537). In this study, it was also found that the effective contribution value for the variable of parental involvement with the learning environment was 13.54% and 15.27%, respectively, while the two predictors simultaneously gave an effective contribution value of 28.81%.Kata kunci: keterlibatan orang tua, lingkungan belajar, prestasi